Community Empowerment A Socio-Legal Perspective on the Role of LPHD Puwesu in East Luwu Regency - Andi Muhammad Idin; Mustaming Mustaming; Takdir Takdir (Har Press Indonesia, 2024)
This study examines community empowerment through the social forestry scheme from sociological and legal perspectives, using a case study of LPHD Puwesu in Matompi Village, East Luwu Regency. The research takes a qualitative approach with a sociolegal design and a sharia-based viewpoint, analyzing formal regulations, social dynamics of local communities, and religious values that influence forest management. The findings reveal that the social forestry scheme has significantly helped strengthen community institutions, boost public participation, and support local economic growth through non-timber forest products. The management rights granted by the government reinforce the community’s legal stance, while the Islamic value-based approach encourages ecological awareness and collective responsibility. However, challenges still exist in market access, managerial capacity, and aligning social norms with regulations. These results highlight the importance of integrating state policies, local values, and spiritual ethics to promote sustainable community empowerment